Economic populism and sovereigntism: the economic supply of European radical right-wing populist parties. Issue 2 (14th March 2020) - Ivaldi, Gilles; Mazzoleni, Oscar
ABSTRACT: While economic issues are increasingly salient in political mobilization by European radical right-wing populist parties, we are still in need of a definition of these parties' economic positions. This paper argues that the economic supply of radical right populist parties is best characterized by a mix of economic populism and sovereigntism, which forms the basis of a common mobilization frame. Economic populism refers to defence of the economic prosperity of the 'heartland' against the elite and immigrants. Economic sovereigntism is seen, on the other hand, as a means of restoring the people's well-being and the nation's prosperity. To illustrate this argument, we conduct a qualitative analysis of five established European populist radical right parties. We demonstrate that, despite different socioeconomic stances, all parties under scrutiny share a common economic populist sovereigntist frame which claims to defend the self-identified economic interests and well-being of the people. We discuss the implications of our research for the broader understanding of populist mobilization.